Dielectric properties of mixed mineral and synthetic ester oil. Issue 9 (28th October 2020) - Mahidhar, Gorla Durga Pawan; Somasundaram Karthikeyan, Amizhtan; Sarathi, Ramanujam; Taylor, Nathaniel; Edin, Hans
Abstract : The dielectric properties of 20% synthetic ester oil mixed with mineral oil were studied for its potential applications as an insulator in transformers. The corona inception voltage of mixed oil under AC and DC voltages was measured by the ultra‐high frequency (UHF) technique. A statistical study of the breakdown voltage of mixed oil under AC, DC and standard lightning impulse voltages was carried out to obtain a database which would be useful for designing transformer insulation. Further, the mixture was subjected to continuous breakdown studies under AC voltage with lightning impulse voltages, at regular intervals and characterised through measurement of interfacial tension, flash point, ionic mobility as well as UV–vis spectroscopy and frequency‐domain spectroscopy studies to understand the liquid's chemical stability. The results of the study have shown that the mixture was stable even after several breakdowns. The ionic mobility and polarisation current have increased, indicating higher losses in the oil. UHF signal energy analysis and phase‐resolved partial discharge analysis have revealed a reduction in discharge activity with mixed oils.